A metal-chelating polymer for chelating zirconium and its use in mass cytometry. (November 2019) - Cho, Hyungjun; Liu, Peng; Pichaandi, Jothirmayanantham; Closson, Taunia L.L.; Majonis, Daniel; Leighton, Patricia L.A.; Swanson, Eric; Ornatsky, Olga; Baranov, Vladimir; Winnik, Mitchell A.
Graphical abstract: Highlights: A metal-chelating polymer was synthesized with deferoxamine, polyethylene glycol, and fluorescein pendant groups and a biotin end-group. The metal-chelating polymer was labeled with Zr, and then the polymer was conjugated to streptavidin-coated polymeric microspheres. The Zr chelating polymers conjugated to the polymeric microspheres was imaged using Imaging Mass Cytometry™ and epifluorescence microscopy. Abstract: Mass cytometry (MC) uses antibodies (Abs) labeled with heavy metal isotopes to monitor biomarker expression on individual cells. Metal-chelating polymers (MCPs) conjugated to the Abs increase the number of metal ions carried per Ab, and this increases the signal generated per Ab. Although the MC detector can detect 134 metal isotopes with unique weight simultaneously, in the current literature a maximum of 43 isotopes have been analyzed simultaneously. Currently available MCPs for MC are well-suited for use with lanthanides and bismuth, but are incompatible with other metals of interest. Here we examine a new MCP with deferoxamine pendant groups designed to chelate Zr ions. Zr has 4 isotopes useful for MC. To overcome the limited water solubility of deferoxamine groups, we introduced pendant polyethylene glycol chains. The polymer also included fluorescein pendant groups, along with a biotin terminal end-group. Once loaded with Zr, the polymers were incubated with streptavidin-coated polystyrene microbead and analyzed using epifluorescence microscopy and imaging MC.